2013
DOI: 10.5038/1827-806x.42.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Fungi isolated from Niedźwiedzia Cave in Kletno (Lower Silesia, Poland)

Abstract: a quarry. The study aimed at first mycological evaluation of the air and the rocks in Niedźwiedzia Cave. Nine species of filamentous fungi and a yeast species were isolated from the air sampled in the cave, whereas from the rocks -nine species of filamentous fungi and two species of yeasts were collected. Rhizopus stolonifer was the species most frequently isolated from the air and from the rocks, while the least isolated from the air was Sclerotinia sclerotiorum. Among the species found in the rock, the least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 15 publications
7
53
0
Order By: Relevance
“…The concentration of spores and bacteria in natural caves are usually much lower than in the mines. For example, in a Niedźwiedzia Cave in the Sudety moutain, which is often visited by tourists, Ogórek et al (2014a) reported the concentration of spores between 123 and 214 CFU/m 3 , while the most commonly isolated fungi were Cladosporium herbarium and Rhizopus stolonifer. Similar results were obtained by Ogórek et al (2014b) examining the air in an artificial underground complex named Włodarz, located inside the massif of Włodarz, within the Owl Mountains, Lower Silesia, Poland.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of spores and bacteria in natural caves are usually much lower than in the mines. For example, in a Niedźwiedzia Cave in the Sudety moutain, which is often visited by tourists, Ogórek et al (2014a) reported the concentration of spores between 123 and 214 CFU/m 3 , while the most commonly isolated fungi were Cladosporium herbarium and Rhizopus stolonifer. Similar results were obtained by Ogórek et al (2014b) examining the air in an artificial underground complex named Włodarz, located inside the massif of Włodarz, within the Owl Mountains, Lower Silesia, Poland.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the findings revealed a great deal of variation between the mould growth on SDA and PDA. This results relates to the submission of [23,24] that a direct relationship exists between the type of culture media and the species composition of microbes isolated from air. It is further evidenced that the outdoor environment is charged with higher microbial loadings as expected with values of 8.93 × 10 2 and 8.33 × 10 2 CFU/m 3 for SDA and PDA media respectively.…”
Section: Bio-aerosol Assessmentmentioning
confidence: 99%
“…Hence, the manuscripts collections (rare books & scholars section) level was selected as the case study in this study. The overall size is 35.33 m × 6.05 m × 3.2 m high (Area = 213.75 m 2 , Volume = 684 m 3 , and A/V ratio = 0.31). Three of the boundary walls are located adjacent to other indoor spaces, hence only one wall is exposed to the external ambient weather with 12 single panel metal window (Fig.…”
Section: Description Of the Case Studymentioning
confidence: 99%
“…Despite their ecological importance, mould may be harmful to not only the indoor stored collections but also the occupants' health [2]. The concentrations of outdoor moulds outnumbered that of indoor with the outdoor-indoor route classified as environmental and biological [3]. While the environmental routes include: ventilation systems, cracks, cervices and other openings, water leakage, the biological ones are: animal dander and human transport.…”
Section: Introductionmentioning
confidence: 99%